2008
DOI: 10.1152/ajpregu.00655.2007
|View full text |Cite
|
Sign up to set email alerts
|

Activation of 5-HT1Areceptors in medullary raphé disrupts sleep and decreases shivering during cooling in the conscious piglet

Abstract: Activation of 5-HT 1A receptors in the medullary raphé decreases sympathetically mediated brown adipose tissue (BAT) thermogenesis and peripheral vasoconstriction when previously activated with leptin, LPS, prostaglandins, or cooling. It is not known whether shivering is also modulated by medullary raphé 5-HT 1A receptors. We previously showed in conscious piglets that activation of 5-HT 1A receptors with (Ϯ)-8-hydroxy-2-(dipropylamino)-tetralin (8-OH-DPAT) in the paragigantocellularis lateralis (PGCL), a medu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 89 publications
(112 reference statements)
4
35
0
Order By: Relevance
“…sleep (11,34). Others have described similar shifts to wakefulness after lidocaine injection into the raphe magnus and rostral ventromedial medulla, a region implicated in antinociception (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…sleep (11,34). Others have described similar shifts to wakefulness after lidocaine injection into the raphe magnus and rostral ventromedial medulla, a region implicated in antinociception (7).…”
Section: Discussionmentioning
confidence: 99%
“…One study in newborn lambs demonstrated that blockade of opioid receptors did not reverse the progressive lengthening of the time to arousal in response to repeated hypoxia exposures (48). Adenosine is released from cells into the extracellular space during hypoxia when oxygen needs no longer match oxygen supply (16) and activation of both GABA A and serotonin 1A (5-HT 1A ) receptors in this region disrupts sleep and promotes wakefulness (11,13,15,34).Our major objective was to determine whether the time to arousal in response to hypoxia and/or its progressive lengthening (habituation) in response to repeated exposure to hypoxia are mediated or modulated by medullary raphe GABAergic mechanisms. We focused on the medullary raphe because this region has been implicated in the pathogenesis of SIDS (46, 60).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Injection of 8-OH-DPAT, a 5-HT 1A receptor agonist, into the rMR blocks BAT thermogenic, metabolic, and tachycardic responses to skin cooling (Fig. 7D) or intravenous injection of leptin (92,107), as well as shivering evoked by cooling or PGE 2 injection into the POA (18,106). These sympathoinhibitory effects of 5-HT 1A receptor agonists through their action in the rMR might be a major pharmacological cause of severe hypothermia observed following systemic administration of such drugs in rats (52), mice (43), and humans (11).…”
Section: Bulbospinal Premotor Signaling From Rmr Neuronsmentioning
confidence: 99%
“…It is hoped that this kind of lecture will become a tradition in future PPTR congresses. The lectures were followed by 10 selected symposia which were devoted to the topics of hyperthermia-induced hyperpnea and thermal panting (Entin et al 2005;White 2006;Fujii et al 2008), TRP channels in body temperature regulation (Tajino et al 2007;Gavva et al 2008), heat stroke (Chen et al 2007), acclimation plasticity and limits of heat tolerance (Taylor 2006, Buckley 2007, Horowitz 2008, Matsuzaki et al 2009), thermoregulation and the sudden infant death syndrome (Blair et al 2008;Brown et al 2008;Hodges et al 2008), control and coordination processes within the thermoregulatory system (Romanovsky 2006;Werner et al 2008), mechanisms and mediators of immune-to-brain communication during inXammation (Weiland et al 2007;Harden et al 2008;Rummel et al 2008), neuronal mechanisms contributing to body temperature regulation (Bautista et al 2007;Tanaka et al 2007;Nakamura and Morrison 2008) and adaptive thermogenesis (Nedergaard et al 2007;Wijers et al 2007). The meeting also included a session of the presentation of six young researcher award winners, two sessions of oral presentation (10 speech) and two poster sessions (126 posters).…”
mentioning
confidence: 99%